Analysis of grammatical transformations in publicistic texts - Ismoilova, Gulshoda Turaboy qizi (The Lingua Spectrum, 2026)
The article provides a comparative analysis of grammatical transformations occurring in publicistic texts translated from Uzbek into English. The theoretical foundations of the concepts of publicism, newspaper language, and media text are explained through the views of scholars in this field, and their role in translation studies is demonstrated. Articles from the website yuz.uz were selected as research material, and the texts published in Uzbek were compared with their English translations. In the course of the analysis, it was determined that there are significant differences in sentence structure and syntactic organization between Uzbek and English. In particular, the formation of word order in both languages, the position of the predicate in the sentence, the placement of the subject and secondary parts of the sentence, as well as the principles of using verb tenses differ from one another. While sentence structure in Uzbek is relatively flexible, strict word order is of primary importance in English. Therefore, these structural differences create certain difficulties in the translation process. In order to overcome these differences and ensure that the translated text is semantically accurate, stylistically fluent, and natural, grammatical transformations are widely used. The results of the analysis showed that among the transformations, changing word order, rearranging sentence elements, and substituting verb tenses according to context are the most frequently used methods. Such changes contribute to increasing the communicative effectiveness of the translated text.